(untitled) (Al-Farooq Journal of Sciences, 2026)
This study aimed to monitor and analyze the structural and sovereign impacts of political division on the management of irregular migration in Libya (2022-2026). The problem stems from the hypothesis that there is a direct correlation between the deepening fragmentation of the government and competing legitimacies, and the decline in the effectiveness of security and legislative responses to migration flows. The absence of a unified central leadership after 2022 led to operational fragmentation and disunity within law enforcement agencies (the Anti-Illegal Immigration Agency and the Border Guard), and a significant statistical gap resulting from the disruption of electronic connectivity and shared databases between the east and west of the country. The research employed a descriptive-analytical approach to dissect these consequences and trace how international agencies and organizations exploited the reality of governmental fragmentation and the lack of a unified negotiating position to impose policies and practices aimed at the "disguised settlement" of migrants within Libya. This effectively transforms the country from a transit state to a permanent destination, directly contradicting the provisions of the existing national law No. (19) of 2010 and infringing upon national sovereignty. The study reached a number of conclusions, most notably: that the absence of a unified negotiating position for the Libyan state legitimized foreign interventions, and that the fragmentation of security agencies weakened border protection, making addressing this issue and restoring a unified decision a fundamental pillar for protecting the sovereignty of the Libyan state.